An electrochemical sensor for the simultaneous determination of rifampicin and isoniazid using a C-dots@CuFe2O4 nanocomposite modified carbon paste electrode. (24th November 2017) - Shiri, Sajad; Pajouheshpoor, Niyoosha; Khoshsafar, Hosein; Amidi, Salimeh; Bagheri, Hasan
Abstract : In this study, a sensitive carbon paste electrode based on a novel nanocomposite of carbon dots/CuFe2 O4 (C-dots@CuFe2 O4 ) was developed for the simultaneous determination of rifampicin (RIF) and isoniazid (INZ). Abstract : In this study, a sensitive carbon paste electrode based on a novel nanocomposite of carbon dots/CuFe2 O4 (C-dots@CuFe2 O4 ) was developed for the simultaneous determination of rifampicin (RIF) and isoniazid (INZ). The morphological and structural properties of the C-dots@CuFe2 O4 were well characterized by transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD). Under the optimized conditions, the voltammetric current increased linearly on increasing the concentration of RIF and INZ in the range of 0.07 to 8.0 and 0.1 to 14.0 μmol L −1, respectively. Moreover, the detection limits for the analytes were calculated to be 0.022 μmol L −1 for RIF and 0.041 μmol L −1 for INZ based on 3 S b / m . The practical applicability of the proposed sensor was examined by evaluating the detection of RIF and INZ in biological fluids and pharmaceutical samples with satisfactory recoveries. The C-dots@CuFe2 O4 /CPE can hold great promise for fast, simple and sensitive detection of RIF and INZ in various real samples.